Description of the female of Actinopus balcarce Ríos-Tamayo & Goloboff, 2018 (Araneae, Actinopodidae), with comments on its natural history - Millenpeier, Micaela (2023)
Trapdoor spiders are known for digging deep burrows into the ground closed with a thick trapdoor. Actinopus balcarce Ríos-Tamayo & Goloboff was described based on two males from Balcarce, Buenos Aires, Argentina. In a recent survey in the type locality, we found females probably belonging to this species. Morphology of the females found allowed us to attribute them to Actinopus balcarce, which are described for the first time. Photographs of the spermathecae are presented along with comments on the natural history of the species. Some morphological insights on the female of this species are also discussed.